RADI-20. CHANGES IN STRUCTURAL BRAIN CONNECTIVITY WITHIN THE FRONTAL LOBES DURING CRANIAL RADIOTHERAPY IN CHILDREN TREATED FOR MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Reddick, Wilburn; Glass, John; Ji, Qing; Conklin, Heather; Harreld, Julie; Robinson, Giles; Gajjar, Amar
Abstract: This study assessed global and regional graph metrics to quantify the impact of craniospinal irradiation (CSI) on structural brain connectivity and efficiency. Fifty medulloblastoma patients (Age at exam 11.0 + 5.1 years [4.9-22.8 years]; 8 low-risk WNT [15 Gy CSI], 20 standard-risk [23.4 Gy CSI], 22 high-risk [36.0 Gy CSI]) were imaged Pre- and Post-CSI using 30 or 64 direction diffusion tensor imaging (DTI) with 2.0 mm spatial resolution. Probabilistic tractography was performed between 82 cortical and sub-cortical brain structures and fractional anisotropy along each tract was used to construct the structural connectome. BrainConnectomeToolbox was used to compare graph metrics Pre- and Post-CSI using a paired T-test (p<0.05 significant) for each cohort. Global graph metrics were not significantly different in any group. High-risk patients demonstrated significantly decreased regional network efficiency throughout the basal ganglia, frontal lobes (superior/middle, medial/lateral orbital, ventrolateral), anterior cingulate, and central cortex. Similarly, standard-risk patients demonstrated significantly decreased regional network efficiency throughout the same structures except the ventrolateral frontal cortex. Strikingly, the low-risk patients showed no significant decreases in regional network efficiency except in the central cortex. Decreased regional network efficiency throughout the basal ganglia, frontal lobes, and anterior cingulate in the high and standard-risk patients would be consistent with the development of later neurocognitive deficits specifically in working memory and executive function. The lack of significant differences post irradiation in the low-risk patients is consistent with less intensive therapy in the WNT sub-group reducing the potential of later neurocognitive deficits in this vulnerable cohort.